2017
DOI: 10.1016/j.drugalcdep.2017.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Extended-release naltrexone reduces alcohol consumption among released prisoners with HIV disease as they transition to the community

Abstract: Background Alcohol use disorders (AUDs) are highly prevalent among persons living with HIV (PLH) within the criminal justice system (CJS). Extended-release naltrexone (XR-NTX) has not been previously evaluated among CJS-involved PLH with AUDs. Methods A randomized, double-blind, placebo-controlled trial was conducted among 100 HIV+ prisoners with AUDs. Participants were randomized 2:1 to receive 6 monthly injections of XR-NTX or placebo starting one week prior to release. Using multiple imputation strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 60 publications
0
43
2
Order By: Relevance
“…PEth results supported these findings. While these findings contrast with findings from a recent study examining the impact of XR-NTX vs. placebo among HIV-positive people released from prison, in which an effect on alcohol was not observed in the main analysis, they are consistent with findings in the afore referenced pilot(25, 26). Interestingly, our findings were observed as an overall group effect with significant differences between groups at each time point during the treatment phase and at 12 months.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…PEth results supported these findings. While these findings contrast with findings from a recent study examining the impact of XR-NTX vs. placebo among HIV-positive people released from prison, in which an effect on alcohol was not observed in the main analysis, they are consistent with findings in the afore referenced pilot(25, 26). Interestingly, our findings were observed as an overall group effect with significant differences between groups at each time point during the treatment phase and at 12 months.…”
Section: Discussioncontrasting
confidence: 81%
“…Since XR-NTX’s Food and Drug Administration’s approval in 2006 for treating alcohol dependence, few studies have evaluated the impact of XR-NTX on HIV-related outcomes. Prior studies are limited to one that enrolled individuals released from prison and a pilot study conducted in HIV treatment settings(25, 26). …”
Section: Introductionmentioning
confidence: 99%
“…This study suggests the risk of hepatotoxicity is minimal in HIV-infected participants treated with naltrexone, and that there are no adverse immunologic or virologic effects of treatment. The safety of extended-released naltrexone (XR-NTX) is further demonstrated in PLH randomized to XR-NTX following release from prison, who experienced no change in hepatic enzymes compared to those receiving placebo in two double-blind, placebo-controlled randomized trials in PLH with alcohol use disorders and those with opioid use disorders [41], nor in the completed trials themselves [12, 42, 43]. HIV/HCV co-infection has no effect on XR-NTX hepatic safety [44].…”
Section: Naltrexonementioning
confidence: 99%
“…As shown in Table 1, two of these studies have used oral naltrexone (NTX) [44,49] and the 5 other used extendedrelease injectable form (XR-NTX) [45][46][47][48]50]. The difference between reported outcomes and a small number of studies has made it difficult to present results in a metaanalysis.…”
Section: Resultsmentioning
confidence: 99%
“…According to Cook et al, 2017 the most common side effects for NTX users were: insomnia (30%), nervousness/anxiety (30%), and nausea (10%). Also, Springer et al, 2017 reported no statistical differences in adverse events between the XR-NTX or placebo groups [50]. In another study by Edelman et al 2019, 51% of participants experienced one or more adverse events with mild to moderate severity and 18% had a serious adverse event.…”
Section: Safetymentioning
confidence: 98%